Prognostic Factors of IVF&ICSI Cycle Cancellation in Patients with Endometriosis-Related Infertility - Kulahci Aslan, Elif; Aslan, Kiper; Cakir, Cihan; Kasapoglu, Isil; Avci, Berrin; Ata, Baris; Uncu, Gurkan (Gynecology Obstetrics & Reproductive Medicine, 2022)
Objective: To elucidate the prognostic factors for intracytoplasmic sperm injection cycle cancellation in patients with endometriosis-related infertility. Study Design: This was a retrospective cohort study and conducted at the Assisted Reproductive Technology center of Uludag University School of Medicine, between the years 2011-2017. The electronic database was screened and infertile patients with endometriosis, without male factor infertility, systemic disease, or undefined adnexal mass, and aged <40 were selected. The endometriosis phenotype of all cycles was classified into three subgroups: superficial endometriosis, ovarian endometrioma and deep infiltrating endometriosis. Cycles were divided into two groups: Group I (Cycle Cancellation) vs. Group II (Embryo transferred). Results: Forty-four cycles were canceled and in 178 cycles, the embryo was able to be transferred. When the groups were compared age and day 3 FSH levels were statistically higher, and anti-Mullerian hormone and antral follicle count were statistically lower in Group I. The presence of adenomyosis was higher in Group I (64% vs. 40% p<0.01). The surgery rate with laparotomy was higher in Group I (54.5% vs. 13.5% p<0.01). Antral follicle count remained as the only independent factor associated with prognoses of the IVF cycle with binary logistic regression analysis. Cancellation rates were similar between the phenotypes of endometriosis. Conclusions: Poor ovarian reserve, advanced age, presence of adenomyosis, and history of laparotomy are negative prognostic factors associated with intracytoplasmic sperm injection cycle cancellation in endometriosis-related infertility. Antral follicle count is the only independent factor in predicting cycle cancellation. The phenotype of endometriosis does not affect the results.